Research on key influencing factors of DT of SMEs in China - Zhang Yujie; Sidah Idris; Jaratin Lily (International Journal Of Modern Education (IJMOE), 2024)
With the new round of technological revolution and industrial transformation is accelerating and leading various aspects of society toward digital transformation (DT). With the widespread application of digital technologies such as big data and cloud computing, the DT process of enterprises is constantly accelerating, and disruptive changes have occurred in product services, business processes, and so on. This article provides a systematic review of existing research on DT and identifies the influencing factors from the organizational level, management level, and environmental level based on the Strategic Change framework of Rajagoralan &Spertizer (1997). Subsequently, an integrated analysis framework was proposed that includes five configuration factors: digital transformation infrastructure, employee skills, management support, market uncertainty, and technology uncertainty. This article not only deepens the understanding of the causal complexity issues behind the success of SMEs’ DT but also provides some beneficial insights for the practice of SMEs’ DT